2019
DOI: 10.1158/0008-5472.can-18-2529
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Scavenger Receptor B1 Is Required for Steroidogenic and Nonsteroidogenic Cholesterol Metabolism in Prostate Cancer

Abstract: Aberrant cholesterol metabolism is increasingly appreciated to be essential for prostate cancer (PCa) initiation and progression. Transcript expression of the high-density lipoprotein-cholesterol receptor scavenger receptor B1 (SR-B1) is elevated in primary PCa. Hypothesizing that SR-B1 expression may help facilitate malignant transformation, we document increased SR-B1 protein and transcript expression in PCa relative to normal prostate epithelium that persists in lethal castration-resistant prostate cancer (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 58 publications
13
41
0
Order By: Relevance
“…Gordon et al also reported increased SR-B1 mRNA expression, but lower LDLR mRNA expression, in prostate cancer vs. matched normal prostatic tissue (23). Our TCGA data analysis showed that SR-B1 mRNA is upregulated and that ABCA1 mRNA is decreased in prostate cancer vs. paired adjacent normal tissue, in agreement with the above studies (22,23).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Gordon et al also reported increased SR-B1 mRNA expression, but lower LDLR mRNA expression, in prostate cancer vs. matched normal prostatic tissue (23). Our TCGA data analysis showed that SR-B1 mRNA is upregulated and that ABCA1 mRNA is decreased in prostate cancer vs. paired adjacent normal tissue, in agreement with the above studies (22,23).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we showed that Alexa568-HDL uptake by TRAMP-C2 cells was in part mediated by SR-B1 ( Fig. 5A, B), a finding that was demonstrated by Gordon et al, in C4-2 prostate cancer cells in which DiI-HDL uptake was partially reduced upon SR-B1 knock down or chemical inhibition by BLT-1 (23). We found that inhibiting de novo cholesterol synthesis in TRAMP-C2 cells by lovastatin led to reduced cell accumulation, which was rescued by HDL treatment in an SR-B1 dependent fashion, suggesting that the cholesterol content of HDL may play a role in the recovery of cell accumulation ( Fig.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations